Analysis of the dynamics of clinical indicators in patients with allergic rhinitis with sensitization to pollen and household allergens using combined allergen-specific immunotherapy - Biletska, S.V.; Dytyatkovska, E.M.; Nikolaychuk, M.A. (Medicni Perspektivi, 2021)
The aim of this study was to evaluate the clinical efficacy of combined allergen-specific immunotherapy (ASIT) in patients with allergic rhinitis (AR) with combined sensitization to pollen and household allergens. To achieve this goal, 49 patients with AR of working age were examined – 35.5±1.5 years with clinical manifestations of seasonal rhinoconjunctival syndrome with a long period of 9.2±1.1 years, among which there were 25 (51.0%) males and 24 (49%) females. All patients were divided into 2 homogeneous groups by age, sex, duration of the disease, the average number of etiologically significant allergens: the main one – 31 patients who received combined ASIT with solutions of pollen and household allergens and a comparison group – 18 patients for whom only pollen allergens were used. Allergological examination included anamnesis, skin tests with pollen allergens (wormwood, ragweed, quinoa, corn, etc.) and household (house dust, mites, epidermal agents) and / or molecular research methods using the ALEX technology. The quantitative integral assessment of the intensity of AR clinical symptoms was calculated as a total score for the main symptoms. The maximum score for the severity of nasal symptoms – 12, eye - 6, total – 18. The results obtained and their analysis indicate that under the influence of ASIT pollen and household allergens in patients there is a significant and reliable decrease in the intensity of clinical manifestations of seasonal rhinoconjunctive syndrome: nasal manifestations – by 52,2%, conjunctival – by 60%, integral – by 54.3% and an increase of 2.2 times in the percentage of patients in the main group with the disappearance or minimization of clinical symptoms of the disease after treatment compared with patients from the comparison group, which convincingly proves and confirms high efficiency of the selected type of therapy in patients with AR in combination with sensitization to pollen and household allergens.